1974
DOI: 10.3733/hilg.v42n09p361
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the origin of the lemon

Abstract: The legend for figure 10 on page 373 does not agree with the orientation of the photograph. To read correctly, the photo should be turned 90 degrees clockwise with the rule at the bottom.Hybrids of 'Eureka' and 'Lisbon' lemons were studied along with their parents and possible ancestral types to investigate the phylogeny of Citrus Zintort (L.) Burm. f. Data on leaf, flower, and fruit characters were collected and analyzed for inheritance of specific characters and for the amount of variability. Leaf and rind-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
2

Year Published

1978
1978
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 6 publications
2
25
0
2
Order By: Relevance
“…Biochemical and molecular data suggest that all lemons are hybrids, with low genotypic variability and high heterozygosity (Malik et al, 1974;Herrero et al, 1996;Roose et al, 1998;Nicolosi et al, 2000). These data also indicate C. medica as one of the ancestral species of limes and lemons.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Biochemical and molecular data suggest that all lemons are hybrids, with low genotypic variability and high heterozygosity (Malik et al, 1974;Herrero et al, 1996;Roose et al, 1998;Nicolosi et al, 2000). These data also indicate C. medica as one of the ancestral species of limes and lemons.…”
mentioning
confidence: 57%
“…They are certainly hybrids, as indicated by the heterozygosity in chromosome markers B, C, D, F L , and G, as well as in 5S and 45S rDNA sites. This pronounced chromosomal heterozygosity can explain the genetic heterozygosity revealed by morphological markers, isoenzyme patterns, essential oils and molecular markers (Malik et al, 1974;Barrett and Rhodes, 1976;Moore and Castle, 1988;Herrero et al, 1996;Nicolosi et al, 2000). It can also explain the meiotic abnormalities reported for C. limon (Longley, 1925;Raghuvanshi, 1962).…”
Section: The Origin Of the Lemonsmentioning
confidence: 83%
“…These results suggest that the species in the two groups including Fortunella species, C. hystrix, C. latipes, C. grandis and C. reticulata, might have been the next ones to have differentiated in an early period. C. limon is, however, included in group 3, since other studies have shown that this species is a hybrid origin (Malik et al 1974;Scora 1975). We also consider that C. limon may be a hybrid derived from species included in group 1, 3 or 6 that contain SS c. C. ichangensis included in group 4 contains SS b which is very close to SS c. It is most likely that this species has been derived from group 3 that has SS c. Since group 1 contains SS c and d, we propose that C. aurantifolia, C. jambhiri, C. paradisi, C. aurantium, C. sinensis, C. tachibana, C. junos, C, limonia, C. nobilis and some cultivars of C. reticulata have hybrid origins.…”
Section: Discussionmentioning
confidence: 99%
“…Based on morphological characteristics, lemon was supposed to be a hybrid of citron (C. medica) and lime (C. aurantifolia) (Swingle, 1943;Malik et al, 1974;Scora, 1975). Barrett and Rhodes (1976) reported that lemon is a trihybrid of citron, pummelo and Microcitrus and had a higher proportion of citron genes.…”
Section: Hierarchical Cluster Analysismentioning
confidence: 99%